Laser metal deposition of pure copper on stainless steel with blue and IR diode lasers. (November 2018) - Asano, Kohei; Tsukamoto, Masahiro; Sechi, Yoshihisa; Sato, Yuji; Masuno, Shin-ichiro; Higashino, Ritsuko; Hara, Takahiro; Sengoku, Masanori; Yoshida, Minoru
Highlights: Blue lasers works efficiently in laser metal deposition compared to infrared lasers. Less laser power is required to produce a copper layer using blue lasers. Copper layers without dilution and defects is produced using blue diode lasers.